2007
DOI: 10.1007/s00383-007-2070-z
|View full text |Cite
|
Sign up to set email alerts
|

Hepatobiliary effects of cholic and lithocholic acids: experimental study in hamsters

Abstract: Etiopathogenesis of biliary atresia remains unknown. Among several theories, one proposes that the disorder may be caused by the toxic effect of monohydroxy bile acids on fetal and neonatal hepatobiliary system. In this paper we evaluated toxic effects produced by ingestion of cholic acid, a trihydroxy bile acid, and lithocholic acid, a monohydroxy bile acid in the hepatobiliary system of a hamster during gestational and perinatal periods. A diet composed by 0.5% cholic acid and 0.25% lithocholic acid was admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Furthermore, accumulation of lithocholic acid has been implicated as a major factor contributing to liver injury because of the inherent cytotoxicity of the hydrophobic bile acids (Deo and Bandiera, ). Additionally, lithocholic acid is thought to participate in the pathogenesis of liver disease and colon cancer (Nagengast et al ., ; Siviero et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, accumulation of lithocholic acid has been implicated as a major factor contributing to liver injury because of the inherent cytotoxicity of the hydrophobic bile acids (Deo and Bandiera, ). Additionally, lithocholic acid is thought to participate in the pathogenesis of liver disease and colon cancer (Nagengast et al ., ; Siviero et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…This induced hepatotoxicity showed similar effects in patients with cholestatic liver disease (Bremmelgaard and Alme, ) and the animal models of cholestasis (Bossard et al ., ; Wang et al ., ). However, liver toxicity produced by the administration of cholic acid or increases in the level of cholic acid could also be induced by deoxycholic acid, the metabolite of cholic acid, rather than cholic acid itself (Siviero et al ., ). Despite this fact, liver toxicity was more related to cholic acid than deoxycholic acid in this study.…”
Section: Discussionmentioning
confidence: 97%
“…Siviero et al . found that cholic acid and lithocholic acid could lead to miscarriage due to inflammation and hepatocyte degeneration 52 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, lithocholic acid, a bacterial metabolite of chenodeoxycholate produced in the intestinal tract, has been implicated as a possible hepatotoxin (Miyazaki et al 1984 ). Glycochenodeoxycholic acid is the most toxic known form of chenodeoxycholate, and has also been shown to induce hepatocellular injury in a dose-dependent manner in human patients (Spivey et al 1993 ; Trottier et al 2012 ; Woolbright et al 2015 ; Siviero et al 2008 ).…”
Section: Discussionmentioning
confidence: 99%